ASSESSMENT OF ACCOUNTING INFORMATION SYSTEM INTEGRATION IN SMALL AND MEDIUM LITHUANIAN ENTERPRISES - Butkevičius, Arūnas (Ekonomika, 2009)
An accounting information system (AIS) plays a key role in providing the financial information for decision making within an organization. The degree of usability and value of the information provided by an AIS largely depends on its timeliness and quality. Both can be improved by the participation of the non-financial stakeholders in its preparation, and by its reuse across multiple business processes. The goal of the research was to investigate AIS integration models in Lithuanian small and medium enterprises, and to determine the prerequisites and obstacles for their integration with the business processes and external information systems. A number of Lithuanian business companies were visited to investigate their information systems. Interviews with the accounting personnel were conducted and the related documentation was inspected. The object of the research was a set of problems concerned with the use of the information provided by the entity’s accounting information system in other functional areas for decision making purposes. Issues involving the preparation and communication of the accounting information for the use of external stakeholders were considered as well.The results of the research showed that the degree of integration of the accounting information systems of small and medium Lithuanian enterprises with their business partners and state institutions remains low, although prerequisites for the integration in some cases are in place.. Obstacles that preclude closer integration with external the systems are the relative inflexibility of the accounting software, the lack of use of the contemporary information and communication technologies, and high investments. To encourage closer integration within the systems, the Service Oriented Architecture should be provided, and be open for Data Integration, easy customization, and extensibility.p>